Perceptions and experiences of Forensic Medicine Department service recipients and providers during male sexual dysfunction assessment following filing for divorce: a qualitative study in Iran: Perceptions and experiences of service recipients and providers during male sexual dysfunction assessment - Safaei, Minoo; Maasoumi, Raziyeh; Mahdavi, Seyed Amirhosein; Ghadirian, Laleh (International Journal of Medical Toxicology and Forensic Medicine, 2023)
Background: In the current era, divorce has become quite commonplace. One of the significant reasons for divorce is sexual dysfunction. the aim of this study was to explore the perceptions and experience of Forensic Medicine Department service recipients and providers during male sexual dysfunction assessment following filing for divorce. Methods: This study was a qualitative study that was analyzed through a content analysis approach. Individual interviews were used for data collection. The data were collected through in-depth semi-structured interviews with Twenty service recipients and nine service providers of Forensic Medicine Department in Tehran from Jan 2022 and ended in March 2022. Results: The analysis of the data led to the extraction of two main categories, including: existing challenges of the forensic medical system in the sexual assessment process with 3 sub-categories (Absence of the plaintiff during the assessment process, sharing a common room with other clients, The psychosocial pressure associated with a Rigi Scan test) and features of desirable evaluation services with 5 Sub-categories (Service delivery to couples, Service delivery by observing ethical principles, confidentiality and human dignity, Comprehensive physical-psychological-communicative assessment, Service delivery that emphasizes informing couples about the road ahead, Provision of services if the authenticity of the sexual problem is proven). Conclusion: Based on the results of the present study, Service recipients expected the claimant to be present throughout the evaluation process and to cover the expenses too. Moreover, they expected a better atmosphere to be available for these individuals and that human dignity and ethical principles be safeguarded. Furthermore, based on their opinions, a comprehensive physical-psychological-communicative assessment was necessary and couples should be informed and aware of the process when they enter it –particularly when the complaint is proven to be unreal, and all evaluations should be performed on both spouses, not just one.